RADT-40. RADIATION-INDUCED CONTRAST ENHANCEMENT FOLLOWING PROTON RADIOTHERAPY FOR LOW-GRADE GLIOMA DEPENDS ON TUMOR CHARACTERISTICS AND IS RARER IN CHILDREN THAN ADULTS. (14th November 2022) - Eichkorn, Tanja; Bauer, Julia; Deng, Maximilian; Bahn, Emanuel; Lischalk, Jonathan; Eva, Meixner; Elisabetta, Sandrini; Regnery, Sebastian; Held, Thomas; Juliane, Hoerner-Rieber; Alber, Markus; Klaus, Herfarth; et al.
Abstract: Proton beam radiotherapy (PRT) is used in the treatment of low-grade glioma (LGG) to mitigate long-term sequelae. Following PRT, increased rates of radiation-induced contrast enhancements (RICE) are suspected but poorly understood. We analyzed consecutive 227 patients (42 children and 185 adults) treated with PRT (54Gy RBE) for LGG from 2010 to 2020 and followed with serial clinical exams and magnetic resonance imaging for in median 5.6 years. Tumors were graded WHO 1 in a minority (n = 22, 12%) of adults, but a majority of children (n = 29, 69%). In contrast, tumors were graded WHO 2 in the majority (n = 160, 87%) of adults and a minority of children (n = 10, 24%). Five-year overall survival following PRT was 81% in adults and 91% in children. The risk of RICE was 5-fold more frequent in adults (25%) versus children (5%) (p = 0.0043). Also, within the adult cohort, RICE risk increases with age (p = 0, 00128). In children and adults, RICE were symptomatic in 50% and 55% (n = 1 and 26) of cases with CTCAE grade 0 in 47% (n = 23), grade 1 in 25% (n = 12), 0% grade 2 (n = 0) and 29% grade 3 (n = 14), respectively. In adults, RICE risk was associated to WHO grading (8% in WHO grade 1 vs. 24% in WHO grade 2, p = 0.026), independent of age (p = 0.44) and irradiation dose (p = 0.005), but not independent of IDH mutational status. These data demonstrate effectiveness of PRT for LGG in both children and adults. The RICE risk is lower in children which are a main target group for PRT and differs with WHO grading.